Penatalaksanaan Dermatitis Numularis pada Perempuan 50 Tahun melalui Pendekatan Dokter Keluarga di Puskesmas Satelit Kota Bandar Lampung: Fakultas Kedokteran, Universitas Lampung Bagian Ilmu Kedokteran Komunitas, Fakultas Kedokteran, Universitas Lampung - Ali, Muhammad Chaidar; Angraini, Dian Isti (Medula, 2025)
Nummular dermatitis (ND) is a chronic inflammatory skin disorder characterized by round, coin-shaped lesions accompanied by itching and inflammation. Although more commonly affecting men aged 55–65 years, it can also occur in other age groups. Several risk factors contribute to its development, including dry skin, irritant exposure, infections, and environmental conditions. Family physicians play a vital role in promotive, preventive, curative, and rehabilitative efforts to improve patients’ quality of life. This study aimed to implement a comprehensive family medicine approach by identifying both internal and external risk factors and providing management based on Evidence-Based Medicine (EBM), emphasizing patient-centered, family-focused, and community-oriented care. This case report involved primary data collection through direct interviews, family anamnesis, physical examinations, and home visits to assess environmental, social, and family aspects. Secondary data were obtained from medical records. A holistic assessment using qualitative and quantitative methods was conducted throughout the management process. A 50-year-old woman presented with complaints of sudden-onset itching on the dorsal feet, knees, and arms persisting for one week, which progressively worsened and was accompanied by skin lesions. Interventions included patient and family education, family conference, pharmacological therapy, and supportive non-pharmacological management. Triggering factors identified in this case were dry skin, repeated trauma, limited health literacy, and occupational exposure. A holistic family medicine approach proved effective in reducing symptoms, enhancing patient knowledge, and preventing recurrence.